Representasi Sistem Nilai dan Perilaku Budaya dalam Tradisi Nganak-Merariq Masyarakat Sasak : Kajian Linguistik Antropologi - Muhamad Wahyu Ramdani; Burhanuddin Burhanuddin; Mahsun Mahsun (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to reveal the role of language in representing the cultural values and social structure of the Sasak community through an analysis of the lingual forms used in the merariq tradition. Based on an anthropological linguistic approach, this study uses a qualitative method with observation techniques, in-depth interviews, and documentation of merariq ritual practices in several Sasak communities in Lombok, West Nusa Tenggara. Data were analyzed using the intralingual matching method with the link-comparison technique to find the relationship between language structure and cultural meaning. The results of the study identified 41 lingual forms classified into six main domains, namely: mbait, beselabar, bekawin, berejap, begawe, and rebaq jengkis. Each domain depicts the stages of the traditional procession that represent the values of courage, sacredness, solidarity, honor, and social integration. Language in the merariq tradition functions not only as a means of communication, but also as a symbolic medium that strengthens the value system, social legitimacy, and cultural identity of the Sasak people. These findings reinforce the theory of Mahsun (2024), Duranti (1997), and Geertz (1973) that language is a cultural practice that shapes collective social consciousness. Theoretically, this research contributes to the development of the study of anthropological linguistics in Indonesia, while practically supporting efforts to preserve ritual languages and local oral traditions. Further research is suggested to explore dialectic variation and cross-cultural comparisons to broaden understanding of the relationship between language, culture, and identity.